Types Of Jewelry Used In Garhwal And Kumaon Regions Of Uttarakhand - Rani, Monika; Kumar, Narendra (International Journal of Psychosocial Rehabilitation, 2024)
The traditional jewelry of Uttarakhand’s culture is well-known. It is also well-known across the globe since visitors come here because they have faith in Uttarakhand. Because of its numerous temples, rich history, and complex customs, Uttarakhand is also known as "Devbhoomi." You may discover a lot of blogs about Uttarakhand on our website. If you haven’t read the article, please do so. Some of the blogs that disseminate information will help you get to know Uttarakhand better. Notable ones are the temples like Kainchi Dham, which is frequented by well-known figures like Steve Jobs, Mark Zuckerberg, and many other notable leaders. We cordially welcome you to our paradise and extend an invitation to visit the lands of God, Uttarakhand, which are a slice of heaven on earth.